Multiple Phenotypic Changes Define Neutrophil Priming - Miralda, Irina; Uriarte, Silvia M.; McLeish, Kenneth R. (Frontiers in Cellular and Infection Microbiology, 2017)
Exposure to pro-inflammatory cytokines, chemokines, mitochondrial contents, and bacterial and viral products induces neutrophils to transition from a basal state into a primed one, which is currently defined as an enhanced response to activating stimuli. Although typically associated with enhanced generation of reactive oxygen species by the NADPH oxidase, neutrophils are activated by priming agents to undergo an array of phenotypic changes involving most neutrophil functions, in addition to enhanced responsiveness to activating signals. This review summarizes the breadth of phenotypic changes associated with priming and reviews current knowledge of the molecular mechanisms behind those changes. We conclude that the current definition of priming is too restrictive. Priming represents activation of neutrophil functions that regulate both the adaptive and innate immune responses, rather than just an enhanced ability to release toxic chemicals that kill microbes.